Deteksi Cemaran Mikroba, Sanitasi, dan Higiene pada Warung Tipat Cantok di Kecamatan Kuta, Bali - Maria Sandikania Mulya; Ni Luh Trisna Darmayanti; I Putu Suparthana (Itepa : Jurnal Ilmu dan Teknologi Pangan, 2026)
Tipat cantok is a traditional Balinese food made from ketupat and boiled vegetables and then served with peanut sauce. Tipat cantok has a high level of starch and water so it is susceptible to being contaminated by microbes such as bacteria and fungi. Some of the microbes that can contaminate this food are Escherichia coli bacteria and yeast mold. This study aims to determine the contamination of pathogenic microbes, sanitation, and hygiene of tipat cantok traders in Kuta District, Badung Regency, Bali. The sampling method was total sampling and interviews with tipat cantok traders. The results of the study are presented in the form of data tables and analyzed descriptively. The parameters observed were total microbes, coliforms, Escherichia coli, yeast mold numbers, sanitary and hygienic practices. The results showed that 62.5 percent of the samples did not meet the requirements for total microbial contamination (<105 colonies/g) and 100 percent did not meet the requirements for yeast mold (<102 colonies/g). All samples showed positive results for coliform and as many as 100 percent of the samples met the requirements for Escherichia coli contamination (<102 colonies/g). The traders have not implemented personal hygiene practices and only implemented some sanitation practices. There are 37.5 percent of traders who store ingredients at the stall table for >4 hours, 100 percent of traders store raw materials >1 day, and 62.5 percent of traders use refillable water. Therefore, it can be concluded that tipat cantok in Kuta District, Badung Regency, Bali is still mostly poorly maintained sanitation and hygiene practices, and has a fairly high level of contamination with pathogenic microbes.